Propositional Proofing Techniques application in Algebraic Structure Research - Muhamad Ali Misri (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2020)
This paper investigates proofing techniques which are used in algebraic structure research and how to apply those techniques. This paper also investigates the reasoning behind the application of the techniques and their effects. The data was collected by reviewing some algebraic structure textbooks used recently. Books reviewed were domestic and foreign books. The results of the review process were noted and documented, and then finally transcribed and coded. The review process of each book was carried out twice. The data obtained were then triangulated, to get the valid data, and eventually used for further analytical purposes. The results obtained show that not all the proofing techniques were used in the proofing process in the algebraic structure research. They tended to use the same technique in every proofing activity. This might be due to mastery of proofing techniques, preferences for certain proofing techniques, lack of information about the development of various proofing techniques. The resulting impact can be identified from the steps of proofing, meanwhile, if it is conducted using another technique, it can reduce the steps, is more acceptable also comprehensible